Texas Interconnection Grid: Economic Optimal Capacity Utilization Rate Evidence - Prentis, Eric L. (International Journal of Energy Economics and Policy, 2015)
For the first time in the literature, the supply and demand model, with 2011-2014 data, is used to analyze the Texas Interconnection grid electricity market. The electric utility industry’s production function, fixed, variable and total cost curve represents the supply curve. The demand curve is the electricity price in the assumed perfectly competitive electricity market. The efficient scale of production is establishedâ€”located where the U-shaped average total cost curve reaches a minimumâ€”and using marginal analysis, where marginal revenue equals marginal cost, to determine the economic optimal capacity utilization rate that maximizes electric utility industry profits. This paper’s aggregate results on the economics of the electric utility market are meaningful, insightful and well-timedâ€”having important electric utility policy implications. Keywords: Economic optimal capacity utilization rate: Efficient scale of production: Capacity planning: Electric utility policy JEL Classifications: G31; G38; H44; K23